The Relationship between Family History of Diabetes and Diabetes by BMI and Age in Korean Men and Women - Ko, Eunna; Sull, Jae Woong (Journal of experimental & biomedical sciences, 2021)
Diabetes is mainly evaluated by fasting blood sugar. The genetic and environmental factors influence the development of type 2 diabetes. In this study, the relationship between diabetes and family history of diabetes in Koreans was analyzed in consideration of body mass index and age. The study subjects were 4,274 subjects who received a medical examination at a university hospital. The main statistical analysis method was multiple logistic regression analysis. In addition, subjects were analyzed by dividing them by gender and the median of age and body mass index. Diabetes prevalence was 8.9% of all subjects, and subjects with a family history of diabetes were 14.5%. The risk of diabetes was 2.80 times higher in subjects with a family history of diabetes than subjects without a family history of diabetes. In addition, in younger subjects, the risk of diabetes was 3.36 times higher in subjects with a family history of diabetes compared with subjects without a family history of diabetes. In this study, the family history of diabetes was significantly associated with diabetes. The relationship between family history of diabetes and diabetes was slightly higher in the younger group than in the older group. In order to obtain an accurate assessment of the association between diabetes and family history of diabetes, further prospective cohort study in the future is necessary.